Profile of Hafiz and Hafizah in Students of the Faculty of Medicine at University of Muslim Indonesia - Mappaware, Nasrudin Andi; Royani, Ida; Mochtar, Shulhana; Makmun, Armanto; Syamsu, Rachmat Faisal; Syahrir, Muhammad; Utami, Nurfika (Lembaga Yasin AlSys, 2025)
Hafiz and hafizah in the Qur'an are interpreted as people who keep something good. This research aims to reveal the profile of hafiz and hafizah students of the Faculty of Medicine, University of Muslim Indonesia. This research is descriptive research with a total sampling design that takes the entire population that meets the sample criteria. The results showed that the data of regional origin of South Sulawesi province had the highest proportion of 73 people (74%). Based on gender, the data obtained from the male gender showed the lowest proportion of 23 people (23%), and the female gender showed the highest proportion of 76 people (77%). Based on the number of memorized juz, the data obtained for the number of memorized 30 juz was the highest proportion of 32 people (32%). Based on the results of the study, it can be concluded that the profile of hafiz and hafizah students of the Faculty of Medicine, University of Muslim Indonesia, based on the origin of the province with the highest proportion of South Sulawesi province, based on female gender shows the highest proportion, and based on the number of memorized juz, namely 30 juz as the highest proportion.